A conceptual framework of macrolevel and microlevel adaptive selling theory, setting a research agenda, and suggested measurement strategies. Issue 3 (3rd July 2019) - McFarland, Richard G.
Abstract: Adaptive selling theory is one of the most important topics studied in the marketing literature. Professor Weitz and colleagues are responsible for foundational research on this topic. Weitz conceptualized adaptive selling at both the macrolevel (treating it as a single construct) and at the microlevel, where he delineates five specific steps that constitute the adaptive selling process. While research exists at both levels, most research has focused on theory development using Weitz's macrolevel conceptualization. Thus, rich avenues for future research exist for microlevel adaptive selling theory. This article first draws a conceptual distinction between macrolevel and microlevel adaptive selling research. Next, it recommends strategies for measurement at both levels. Finally, using the ISTEA model, this article organizes divergent research into a microlevel framework and a research agenda with specific questions for future research is developed.